Membudayakan Keterampilan Menulis pada Mading Kelas untuk Melatih Kreativitas Siswa - Arnelia Dwi Yasa; Denna Delawanti Chrisyarani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Writing is an inseparable activity from everyday human life. Writing skills can be fostered from diligent reading. One of the reading media as well as the media for pouring student work is mading. Mading is a vehicle for applying students' abilities, especially in the field of writing. MI Manbaul Ulum Karangduren is a school located in Malang Regency. The school does not yet have a class bulletin board containing student work. Thus, the opportunity for students to develop their creativity in writing is hampered. Efforts are needed to improve writing skills for students to build a reading culture. One way is to publish bulletin as a teaching aid and coaching. Through bulletin board, it is hoped that students can have creativity in writing. The results of community service activities show that students' writing skills have improved. The average value of N-Gain Creativity Test scores 0.73 in the high category. This shows the level of effectiveness of the treatment has a high effect on the post test.